Enzymatic synthesis of Tinuvin - Schroeder, M. (2007)
Coupling of 3-(3-tert-butyl-4-hydroxyphenyl) propionic acid methylester to 1H-benzotriazole using a laccase from Trametes hirsuta was studied. The potentially resulting coupling product Tinuvin 1130 is an important UV-absorber used in polymer based materials. Oxidation of the phenol by the laccase led to homomolecular coupling reactions while the laccase did not attack 1H-benzotriazole. Due to the homomolecular reaction of the phenol in the presence of laccase coupling of phenol and 1H-benzotriazole was only observed when 1H-benzotriazole was applied in four-fold molar excess. The reaction was monitored by UV/vis spectroscopy, TLC and MS (ion trap) analysis. Coupling of 1H-benzotriazole took place in ortho position according to the postulated mechanism.